Computationally simulating the hydrothermal mineralizing system involved in the Laochang Pb-Zn deposit, Gejiu ore district, Yunnan, China: an example of pore-fluid convection controlled mineralization - Liu, Gaozhi; Zhao, Chongbin (Frontiers in Earth Science, 2024)
The Laochang Pb-Zn deposit can be typically considered as a hydrothermal mineralizing deposit in the Gejiu ore district. Although extensive studies were conducted to understand the mineralizing system associated with the Laochang Pb-Zn deposit through using the traditional geoscience methods, the mineralizing process involved in this deposit has not been justified in a strictly scientific manner to date. In this article, the hydrothermal mineralizing mechanism of the Laochang Pb-Zn deposit is computationally simulated through using the dual length-scale approach associated with the finite element method (FEM). The related computationally simulating outcomes have revealed the following understanding: (1) the pore-fluid convection provides a continuous source of mineralizing fluid and material for the Laochang Pb-Zn deposit; (2) the convective flow of pore-fluid is the primary dynamic mechanism, which controls the temperature, chemical species and pore-fluid velocity distributions in the Laochang Pb-Zn deposit; (3) the localized structure plays a key role in controlling the localized pore-fluid flow pattern, which can further control the location and grade of the orebody in the Laochang Pb-Zn deposit; (4) the dual length-scale approach associated with the FEM is very useful for dealing with the computational simulation of the hydrothermal mineralizing mechanism involved in the Laochang Pb-Zn deposit.